Risk Factors Associated with Birth Asphyxia in Phramongkutklao Hospital - Chayasak Pitsawong; Prisana Panichkul (The Royal Thai College of Obstetricians and Gynaecologists, 2011)
Objective: To determine the risk factors for birth asphyxia Materials and Methods: After obtaining the approval from the Institutional Review Board, a retrospective case-control study recruited 450 women who delivered at Phramongkutklao Hospital between January 1, and December 31, 2009 were recruited by consecutive selection. The study sample comprised 150 women who delivered newborns with an APGAR score at 1 minute of 7 or less, while the control comprised 300 women who delivered newborns with an APGAR score at 1 minute more than 7. The risk factors for birth asphyxia were determined. Result: The risk factors associated with birth asphyxia included moderate to thick meconium (OR 5.51, 95% CI 2.58-11.77), breech presentation (OR 4.53, 95% CI 1.72-11.92), birth weight < 2,500 grams (OR 2.46, 95% CI 1.4-4.29), sedation with morphine or pethidine (OR 2.29, 95% CI 1.37-3.84) and preterm delivery (OR 2.08, 95% CI 1.24-3.51).Conclusion: Most risk factors associated with birth asphyxia can be prevented. Therefore the correct, quick and accurate diagnosis and proper management can reduce severe birth asphyxia.